2018
DOI: 10.1371/journal.pone.0207818
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence and trends among a U.S. national sample of women of reproductive age in rural versus urban settings

Abstract: U.S. smoking prevalence is declining at a slower rate in rural than urban settings and contributing to regional health disparities. Cigarette smoking among women of reproductive age is particularly concerning due to the potential for serious maternal and infant adverse health effects should a smoker become pregnant. The aim of the present study was to examine whether this rural-urban disparity impacts women of reproductive age (ages 15–44) including pregnant women. Data came from the ten most recent years of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…A Canadian study showed that trends in maternal smoking during pregnancy were not consistent across groups with different educational backgrounds [5]. In addition, a 2007-2016 US study found higher smoking prevalence among rural women of reproductive age compared to their urban counterparts [6]. The results of another US study suggest that women who were aged 20-24, American Indian/Alaska Natives, high school educated or less, and had Medicaid coverage had the highest prevalences of smoking before, during, and after pregnancy [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Canadian study showed that trends in maternal smoking during pregnancy were not consistent across groups with different educational backgrounds [5]. In addition, a 2007-2016 US study found higher smoking prevalence among rural women of reproductive age compared to their urban counterparts [6]. The results of another US study suggest that women who were aged 20-24, American Indian/Alaska Natives, high school educated or less, and had Medicaid coverage had the highest prevalences of smoking before, during, and after pregnancy [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that smoking cessation after becoming pregnant is associated with a reduced risk of preterm birth [8]. In past research, women who were younger than 20, Asian/Pacific Islander, had more than 12 years of education, had private insurance, and lived in urban areas were most likely to quit smoking during pregnancy [6,7]. However, despite a recent increase in prenatal quitting rates, only half of women quit smoking during pregnancy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Public health surveillance has identified geographical differences in smoking prevalence as well as smoking-related morbidity of 11 and mortality between urban and rural populations [4][5][6][7][8]. Rural populations have significantly higher prevalence of smoking compared to their urban counterparts [4,5] and consume a higher number of cigarettes per day [6]. Additionally, despite an overall reduction in cancer diagnoses [7], rural populations experience a higher likelihood of lung cancer diagnosis and death than urban populations-a pattern likely tied to the elevated prevalence of smoking in rural settings [3].…”
Section: Introductionmentioning
confidence: 99%
“…4 Women's smoking rates overall, and in pregnancy, have slowly declined and rural and lower-income women continue to have higher rates of smoking and lower quit rates in pregnancy. [5][6][7] In addition national birth certificate data from 2014 shows 10.1% women smoked just prior to pregnancy and 8.4% reporting smoking in pregnancy. Of these smokers in pregnancy about one in five women had quit between the first and third trimester.…”
Section: Introductionmentioning
confidence: 99%
“…Of these smokers in pregnancy about one in five women had quit between the first and third trimester. 6 Pregnancy can serve as a catalyst for mothers to change health behaviors to benefit their child. 8 Mothers alter diet, alcohol, and tobacco use in response to being pregnant.…”
Section: Introductionmentioning
confidence: 99%